Necropsy findings in lysinuric protein intolerance. Issue 4 (April 1996) - McManus, D T; Moore, R; Hill, C M; Rodgers, C; Carson, D J; Love, A H
Abstract : Lysinuric protein intolerance (LPI) is a rare autosomal recessive inborn error of metabolism, characterised by defective transport of the cationic amino acids lysine, arginine and ornithine. To date there are few reported necropsy cases. This report describes the necropsy findings in a 21 year old female patient originally diagnosed as having LPI in 1973. Liver function tests deteriorated and immediately before death jaundice, hyperammonaemia, coma, metabolic acidosis, and a severe bleeding diathesis developed. At necropsy, there was micronodular cirrhosis of the liver with extensive fatty change in hepatocytes. The lungs showed pulmonary alveolar proteinosis. Immunofluorescence and electron microscopy revealed the presence of a glomerulonephritis with predominant IgA deposition. These necropsy findings reflect the spectrum of lesions reported in LPI, providing further evidence of an association between this condition and pulmonary alveolar proteinosis, cirrhosis and glomerulonephritis.